VEGFR1+ metastasis-associated macrophages contribute to metastatic angiogenesis and influence colorectal cancer patient outcome - Freire Valls, Aida; Knipper, Karl; Giannakouri, Evangelia; Sarachaga, Víctor; Hinterkopf, Sascha; Wührl, Michael; Shen, Ying; Radhakrishnan, Praveen; Klose, Johannes; Ulrich, Alexis; Schneider, Martin; Augustin, Hellmut; et al. (Clinical cancer research, 2019)
PURPOSE: To investigate the clinical relevance of macrophages in liver metastasis of colorectal cancer and their influence on angiogenesis and patient survival. Moreover to evaluate specific blood monocytes as markers of disease recurrence.Experimental design: In a mouse model with spontaneous liver metastasis, the angiogenic characteristics of tumor- and metastasis (MAM)-associated macrophages were evaluated. Macrophages and the vasculature from 130 primary tumor (pTU) and 123 patients with liver metastasis were assessed. In vivo and in human samples, the clinical relevance of macrophage VEGFR1 expression was analyzed. Blood samples from patients (n = 157, 80 pTU and 77 liver metastasis) were analyzed for assessing VEGFR1-positive (VEGFR1+) cells as suitable biomarkers of disease recurrence. - RESULTS: The number of macrophages positively correlated with vascularization in metastasis. Both in the murine model as well as in primary isolated human cells, a subpopulation of MAMs expressing VEGFR1 were found highly angiogenic. While VEGFR1 expression in pTU patients did not predict prognosis; high percentage of VEGFR1+ cells in liver metastasis was associated with worse patient outcome. Interestingly, VEGFR1+-circulating monocytes in blood samples from patients with liver metastasis not only predicted progression but also site of recurrence. - CONCLUSIONS: Our findings identify a new subset of proangiogenic VEGFR1+ MAMs in colorectal cancer that support metastatic growth and may become a liquid biomarker to predict disease recurrence in the liver.